Pelatihan Digitalisasi Quiz Menggunakan Quizizz untuk Pengajar SMP Johanes Bosco - Alexander Bryan F N; Antonius Dika Prasetya; Bintang Ilham (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
This study aims to explore the understanding and advantages of using Quizizz as an effective learning tool at Johanes Bosco Middle School. Through this dedication, the teachers at SMP Johanes Bosco are given the opportunity to get to know and understand the benefits of Quizizz in improving the quality of learning. The results of this experience show that Quizizz is able to provide significant benefits by providing interesting interactive questions, direct feedback to students, and fun learning experiences. Teachers feel more confident and motivated to integrate Quizizz into their daily learning, with the hope of increasing their students' understanding and academic achievement. This research provides a better understanding of the importance of Quizizz in the educational context, as well as contributes to improving learning at SMP Johanes Bosco.